Acclimation to Very Low CO2: Contribution of Limiting CO2 Inducible Proteins, LCIB and LCIA, to Inorganic Carbon Uptake in Chlamydomonas reinhardtii. Issue 4 (21st October 2014) - Wang, Yingjun; Spalding, Martin H.
Abstract : Two complementary inorganic carbon uptake systems show distinct functions in the CO2 -concentrating mechanism and both are essential for limiting CO2 acclimation . Abstract: The limiting-CO2 inducible CO2 -concentrating mechanism (CCM ) of microalgae represents an effective strategy to capture CO2 when its availability is limited. At least two limiting-CO2 acclimation states, termed low CO2 and very low CO2, have been demonstrated in the model microalga Chlamydomonas reinhardtii, and many questions still remain unanswered regarding both the regulation of these acclimation states and the molecular mechanism underlying operation of the CCM in these two states. This study examines the role of two proteins, Limiting CO2 Inducible A (LCIA; also named NAR1.2) and LCIB, in the CCM of C. reinhardtii . The identification of an LCIA-LCIB double mutant based on its inability to survive in very low CO2 suggests that both LCIA and LCIB are critical for survival in very low CO2 . The contrasting effects of individual mutations in LCIB and LCIA compared with the effects of LCIB - LCIA double mutations on growth and inorganic carbon-dependent photosynthetic O2 evolution reveal distinct roles of LCIA and LCIB in the CCM . Although both LCIA and LCIB are essential for very low CO2 acclimation, LCIB appears to function in a CO2 uptake system, whereas LCIA appears to be associated with a HCO3 − transport system. The contrasting and complementary roles of LCIA and LCIB in acclimation to low CO2 and very low CO2 suggest a possible mechanism of differential regulation of the CCM based on the inhibition of HCO3 − transporters by moderate to high levels of CO2 .